Revisão taxonômica e filogenia de Pamphorichtlys Regan, 1913 (Cyprinodontiformes; Poeciliidae) - Figueiredo, Carlos Augusto Assumpção de (1997)
Pamphorichthys diagnosis is based on twenty-seven apomorphic character states, mainly from the pelvic fins. Among the autapomorphies of the genus, eleven are reductive characters due to the species miniaturization. The included species are: Pamphorichthys minor (Garman), P. scalpridens (Garman), P. hollandi (Henn) and P. araguaiensis Costa Limia heterandria Regan is confirmed as a member of Limia based on three synapomorphies and not related to Pamphorichthys as suggested by recent authors. Pamphorichthys hasemani is the sister group of the other species in the genus, that comprises a trichotomy formed by Pamphorichthys minor, P. araguaiensis and P. scalpridens + P. hollandi. The sister group relationship between Limia and Pamphorichthys is corroborated by four synapomorphies, three of them are new. An osteological description of the genus' species is provided and each species is redescribed and diagnosed. Distribution maps, synonymy lists, and a brief history of the genus and each species systematics are also provided.